Impacts of gene variants on drug effects-the foundation of genotype-guided pharmacologic therapy for long QT syndrome and short QT syndrome - Zhao, Zhihan; Zang, Xiaobiao; Niu, Kerun; Song, Weifeng; Wang, Xianqing; Mügge, Andreas; Aweimer, Assem; Hamdani, Nazha; Zhou, Xiao-Bo; Zhao, Yonghui; Akın, Ibrahim; El-Battrawy, Ibrahim (EBioMedicine, 2024)
The clinical significance of optimal pharmacotherapy for inherited arrhythmias such as short QT syndrome (SQTS) and long QT syndrome (LQTS) has been increasingly recognised. The advancement of gene technology has opened up new possibilities for identifying genetic variations and investigating the pathophysiological roles and mechanisms of genetic arrhythmias. Numerous variants in various genes have been proven to be causative in genetic arrhythmias. Studies have demonstrated that the effectiveness of certain drugs is specific to the patient or genotype, indicating the important role of gene-variants in drug response. This review aims to summarize the reported data on the impact of different gene-variants on drug response in SQTS and LQTS, as well as discuss the potential mechanisms by which gene-variants alter drug response. These findings may provide valuable information for future studies on the influence of gene variants on drug efficacy and the development of genotype-guided or precision treatment for these diseases.
Online verfügbar: 22. April 2024, Artikelversion: 22. April 2024
Gesehen am 28.11.2024